2017
DOI: 10.5455/medarh.2017.71.246-250
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Treatment of Breakthrought Pain (BTcP) in Palliative Care

Abstract: Introduction:This research was to follow characteristics of breakthrough pain caused by cancer (BTcP) and other most common sympthoms (ESAS) at patients in advanced stage of cancer disease in palliative care.Patients and methods:Prospective study included 433 patients which were treated in Palliative Care Centre in UKC Tuzla, Bosnia and Herzegovina. Group 1 was consisted of 353 patients whose basal cancer pain of intensity 4-7 NRS was treated weak opiates (basal analgetic- fixed combination of tramadol/paracet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…62 The most common sites of metastases are the vertebrae, pelvis, long bones, and ribs 63 and innocuous movement, bumps or falls may result in painful pathological fractures, 1 which might reduce mobility and increase anxiety, significantly worsening QoL. 64 Many breakthrough pain episodes of greater intensity in the advanced stages of cancer are due to bone pain caused by metastasis 17 and require additional proper therapy. Albiach et al 76 collected data from patients with metastatic bone disease and BTcP and demonstrated that primary cancer was mainly localized in the lungs and prostate (85 out of 386 patients or 22%), and BTcP occurred spontaneously and suddenly with high pain intensity in 70.6% of cases.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…62 The most common sites of metastases are the vertebrae, pelvis, long bones, and ribs 63 and innocuous movement, bumps or falls may result in painful pathological fractures, 1 which might reduce mobility and increase anxiety, significantly worsening QoL. 64 Many breakthrough pain episodes of greater intensity in the advanced stages of cancer are due to bone pain caused by metastasis 17 and require additional proper therapy. Albiach et al 76 collected data from patients with metastatic bone disease and BTcP and demonstrated that primary cancer was mainly localized in the lungs and prostate (85 out of 386 patients or 22%), and BTcP occurred spontaneously and suddenly with high pain intensity in 70.6% of cases.…”
Section: Reviewmentioning
confidence: 99%
“…Most BTcP episodes peak in intensity within a few minutes and last for 30-60 minutes. 12,[15][16][17] Idiopathic or spontaneous BTcP occurs in the absence of a relationship to any specific, recognizable cause, whereas incident pain can be volitional if triggered by a voluntary act (e.g. walking, weightbearing, food/liquid ingestion, and changes in sleeping position) or non-volitional if related to an involuntary act (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is responsible for both incident and movement-induced BTcP. 134 Correct management of BTcP allows for significant improvement in the QoL of these patients. [135][136][137] TIRF is the treatment of choice for BTcP due to its pharmacological properties, including rapid onset, increased potency and short half-life.…”
Section: Commentmentioning
confidence: 99%
“…The selection of an appropriate on-demand IR opioid depends on a number of factors: the patient's physical condition and dexterity (which affect administration and tolerance) and likelihood of adherence/abuse; and the medication's onset and duration of action and route of administration (38,75). For example, oral tramadol may be efficacious in cancer patients experiencing breakthrough pain of mild to moderate intensity (76); fentanyl may provide a greater level of pain relief in a shorter time frame (77). Because of a lack of bioequivalence between different fentanyl formulations, individualized dose-titration may be needed for balancing efficacy with tolerability and avoiding overdose (75).…”
Section: Immediate-release (Ir) Vs Sustained-release (Sr) Formulationsmentioning
confidence: 99%